ANALISIS PELAKSANAAN QUALITY CONTROL DALAM MENINGKATKAN KUALITAS PRODUK (STUDI PADA UD TOHU SRIJAYA KOTA BATU) - Elly Lestari; Nosi Noviah (OPTIMA, 2022)
The purpose of this study was to analyze the application of a product quality control system at UD Tohu Srijaya and to determine the causes of product damage (defects) at the company. This research uses descriptive quantitative approach, using statistical tools for Statistical Process Control (SPC), namely check sheets, control charts, Pareto diagrams and cause and effect diagrams or fishbone diagram. Data sources consist of primary and secondary data. The research methods include documentation, observation, interviews and literature study. The results showed that it is related to the products produced by UD Tohu Srijaya in the form of kitchen utensils, one of which is the product that is supervised is a tissue box holder. Based on the check sheet, it can be seen that the total number of production is 3807 and the number of defective products is 130 which is divided into three parts, namely asymmetric as many as 43 products, stripes as many as 39 products, and scuffs as many as 48 products. Based on the results of the p control chart analysis, the percentage in January - December is still under control, except in June the percentage is 0% because in that month there is no production of tissue boxes. So it can be said that the damaged product is still within control limits. The Pareto diagram shows that the most dominant product damage is blisters which have a percentage of 36.92%. Then based on the cause efect diagrams or fishbone diagram it is known that the factors that cause the product to be damaged come from humans, materials, methods, and also other factors.